2021
DOI: 10.3390/ijms22073655
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol-17β Regulates Expression of Luteal DNA Methyltransferases and Genes Involved in the Porcine Corpus Luteum Function In Vivo

Abstract: The corpus luteum (CL) is a temporary endocrine gland vital for pregnancy establishment and maintenance. Estradiol-17β (E2) is the major embryonic signal in pigs supporting the CL’s function. The mechanisms of the luteoprotective action of E2 are still unclear. The present study aimed to determine the effect of E2 on luteal expression of factors involved in CL function. An in vivo model of intrauterine E2 infusions was applied. Gilts on day 12 of pregnancy and the estrous cycle were used as referential groups.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Our findings are also consistent with a report indicating that the expression of DNMTs in the human endometrium decreased during the secretory phase and was reduced by E 2 and P4 in endometrial stromal cells [ 42 ]. Similarly, our recent findings indicate that E 2 controlled DNMT expression in the porcine corpus luteum in vivo and changes in their abundance were significant during pregnancy [ 31 ]. Interestingly, recent studies have indicated that E 2 can affect the expression of DNMTs via a complex mechanism involving a number of co-regulators [ 43 ].…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Our findings are also consistent with a report indicating that the expression of DNMTs in the human endometrium decreased during the secretory phase and was reduced by E 2 and P4 in endometrial stromal cells [ 42 ]. Similarly, our recent findings indicate that E 2 controlled DNMT expression in the porcine corpus luteum in vivo and changes in their abundance were significant during pregnancy [ 31 ]. Interestingly, recent studies have indicated that E 2 can affect the expression of DNMTs via a complex mechanism involving a number of co-regulators [ 43 ].…”
Section: Discussionmentioning
confidence: 71%
“…The endometrial DNMT1 , DNMT3A , and DNMT3B gene expression were determined using quantitative PCR (qPCR, real-time RT-PCR), as described previously [ 31 ]. Detailed information of qPCR procedure has been provided in Supplementary Information.…”
Section: Methodsmentioning
confidence: 99%
“…The role of E2 in the luteal function in pigs is not clearly understood. Whereas some studies report its beneficial effect on CL function [ 45 , 46 ], others suggest E2 to play a role in CL regression [ 22 , 47 ]. Our results suggest that actions of E2 must be dependent upon the expression of E2-metabolizing enzymes, which differ in abundance during the estrous cycle.…”
Section: Discussionmentioning
confidence: 99%
“…The final 20-µL reaction volume comprised the TaqMan Gene Expression Master Mix and 50 ng of cDNA. Relative gene expression was normalized against the reference gene PPIA 7 , 46 (assay ID: Ss03394782_g1). The relative gene expression levels were determined by following the method outlined by Livak and Schmittgen 47 , using the comparative cycle threshold (2 -ΔΔCt ) approach.…”
Section: Methodsmentioning
confidence: 99%